IMPLEMENTASI DESAIN MODEL ASSURE DALAM PEMBELAJARAN NOTASI BALOK WARNA UNTUK SISWA KELAS 1 SD - Elizabeth Suryani Ongko; Martadi Martadi; Trisakti Trisakti; Yoyok Yermiandhoko; Warih Handayaningrum (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to develop a teaching material for learning block notation. Based on the results of interviews with several music teachers at private elementary schools in Surabaya, researchers obtained data that there are always students who have difficulty understanding block notation in all private elementary schools that provide block notation material for class students. 1 SD. Therefore, the researcher wants to design a block notation learning material that is interesting and makes it easier for students to understand block notation. The learning design made by the researcher uses the ASSURE model design by paying attention to aspects of child cognitive psychology and color psychology. The results of the design are black block notation images, color block notation images along with hand movements and audio as a unitary block notation teaching material. The results of the design were then tested on grade 1 students at Sampoerna Academy Elementary School and the results showed that 90% of children were interested in the color block notation learning design and it was easier to understand the material.